2010
DOI: 10.1038/ismej.2010.143
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sulfate-reducing bacterial populations during the onset of black band disease

Abstract: Factors that facilitate the onset of black band disease (BBD) of corals remain elusive, though anoxic conditions under the complex microbial mat and production of sulfide are implicated in necrosis of underlying coral tissues. This study investigated the diversity and quantitative shifts of sulfatereducing bacterial (SRB) populations during the onset of BBD using real-time PCR (RT-PCR) and cloning approaches targeting the dissimilatory (bi)sulfite reductase (dsrA) gene. A quantitative-PCR (qPCR) assay targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 24 publications
5
51
1
1
Order By: Relevance
“…This is in accordance with previous work that has shown that different coral species harbour different microbial communities [11,19,21,22]. Furthermore, previous work has shown that the microbial communities associated with diseased corals can differ substantially to the communities associated with healthy corals [28,32,[76][77][78]. Although both samples were retrieved from above corals that appeared healthy, without any visible signs of tissue necrosis, colour loss or disease, there remains the possibility that the health status of the two sampled coral niches was different.…”
Section: Taxonomysupporting
confidence: 81%
See 1 more Smart Citation
“…This is in accordance with previous work that has shown that different coral species harbour different microbial communities [11,19,21,22]. Furthermore, previous work has shown that the microbial communities associated with diseased corals can differ substantially to the communities associated with healthy corals [28,32,[76][77][78]. Although both samples were retrieved from above corals that appeared healthy, without any visible signs of tissue necrosis, colour loss or disease, there remains the possibility that the health status of the two sampled coral niches was different.…”
Section: Taxonomysupporting
confidence: 81%
“…For instance, Vibrio species have been implicated in several coral diseases. Vibrio shiloi and Vibrio coralliilyticus have been shown to be involved in coral bleaching [2,73,74], Vibrio owensii was found to cause Montipora white syndrome [75] and a consortium of Vibrio are believed to be involved in yellow band disease [75][76][77][78][79]. However, while the roles of V. shiloi and V. coralliilyticus in bleaching has been confirmed by several studies [2,73,74], it is still not clear whether other Vibrio species found in association with diseased corals [75][76][77][78][79] are the disease-causing agent, or opportunistic colonisers that most efficiently exploit already compromised corals [70].…”
Section: Taxonomymentioning
confidence: 99%
“…Quantitative PCR assay for quantifying dsrA DNA was pooled from four replicate 96-well gradient plates (B800 ml of culture) and Taqman (Life Technologies, Grand Island, NY, USA) quantitative PCR was used to quantify dsrA gene abundance using previous methods with some modifications (Leloup et al, 2007;Bourne et al, 2011;Supplementary Methods).…”
Section: Methodsmentioning
confidence: 99%
“…Penyakit karang diketahui mempunyai kontribusi yang signifikan terhadap menurunnya kondisi ekosistem terumbu karang (Harvell et al, 2004;Sutherland et al, 2004;Weil et al, 2006). BBD merupakan salah satu jenis penyakit karang bersifat virulen yang ditemui menyerang pada banyak jenis karang scleractinia dan merupakan salah satu penyebab kerusakan pada ekoisistem karang (Frias-lopez et al, 2004;Bourne et al, 2011). BBD hampir dapat dijumpai di seluruh ekosistem karang dunia seperti Indo-pasifik, laut karibia, samudera hindia dan atlantik.…”
Section: Pendahuluanunclassified